An??lise dos stakeholders: um estudo de caso de um banco de cr??dito consignado - Xavier, Daniel Laurentino de Jesus (2010)
In the competitive market that we are living, it is increasingly important to understand why some firms have a better competitive position than others. For many scholars one of the factors that impact on corporate performance is related to how organizations treat their stakeholders. The stakeholder theory argues that firms should identify who are the stakeholders and determine how they influence. This knowledge indicates elements that enable the company to define more effective strategies for positioning and relationship. The characterization of the stakeholders is important in any market, including emerging markets such as payroll deduction loan, which shows strong growth, increasingly attracting the interest of banks, including those that traditionally did not invest in this type of credit. In the study, we sought to characterize the most important stakeholders who act in a payroll deduction loan bank using different approaches according to the models of stakeholder salience by Mitchell, Agle and Wood (1997), the model of influence strategies by Frooman (1999) and the model of relationship analysis proposed by Friedman and Miles (2002). This is a descriptive study and was done through a case study of a mid-size national bank that acts significantly in the payroll deduction loan sector. The approach for the research was qualitative, through the analysis of semi-structured interviews and documentation on the firms that is object of study. The result of the research suggests that analysis from different views of the stakeholders is interesting for its characterization. The data indicate that the covenants, regulatory agencies and financial partners are definitive stakeholders, but only financial partners have compatible interests with the organization, indicating that they tend to protect the relationship with the company and use cooperative strategies, while the others two have a relationship of risk and tend to use coercion as strategy. The data also suggest that customers, employees and exclusive correspondents are dominant stakeholders, so for the employees and for exclusive correspondents is expected to use cooperation strategies and the protection of the relationship with the company. As for customers, the data suggests that these stakeholders tend to coerce the firm and have a concession relationship that is constantly threatened. Finally the preferred correspondents and shareholders were both classified as dangerous. The data also indicate that for these stakeholders are expecting a direct strategy of coercion, but showing a tendency to protect the relationship with the company.